An empirical study of the awareness and access of financial inclusion schemes in mangaluru city, karnataka - Maroor, J.P.; Pushpanathan, A.; Baliga, V.B. (SDM PG Centre for Management Studies and Research, Mangaluru., 2016)
Financial inclusion is the delivery of financial services or products at inexpensive costs to the underprivileged and lower income sections of the society. By providing these financial services to the people with no access to banking activities, country can achieve the goal of financial inclusion. RBI and Government of India has taken many steps and introduced many schemes in order to bring the people of the unbanked area under financial inclusion. Recently Government has come up with several financial inclusion schemes, among all those schemes Pradhan Mantri Jan Dhan Yojana has given big push for the financial inclusion in the country. This was followed by the two life insurance scheme with low premium amount and one pension scheme. Government also introduced Pradhan Mantri Mudra Yojana which will provide financial assistance to the small business units. The main objective of this study was to study the awareness of financial inclusion schemes among the customers of Mangaluru branch of a nationalized Bank. The Study was conducted to make an attempt to understand the preference and awareness of financial inclusion among the customers of Mangaluru branch of a nationalised Bank. After getting the responses from the bank customers it was found that, majority of the people are aware about PMJDY followed by the two insurance schemes of financial inclusion. 20 percent of the people opted for both the insurance schemes and about 59 percent of the people who have enrolled for these insurance schemes are those who didn't had any insurance policy before. It was also found that majority of the respondents came to know about these schemes from the advertisement given by the Government, so it is evident that advertisement given by the Government on financial inclusion schemes has been effective. From the responses of PMJDY account holders it was found that, account holders are not operating their account frequently, most of the respondents are operating their account semi-annually. There was lack of awareness among the respondents about the Atal Pension Yojana and Pradhan Mantri Mudra Yojana loan. The number of people enrolled for APY was just 05 in the bank. It was found that the bank has given majority of Pradhan Mantri Mudra Yojana loan under Shishu scheme followed by the Tarun scheme.
Keywords: Financial inclusion; PMJDY; Financial Literacy; Economic Growth